Conception of culture and nursery: a social-semiotic analisis of scientific production - Luiz Henrique Chad Pellon; Daniella Barros Oliveira Cézar (Universidad de Alicante, 2012)
This study aims to identify the concepts of culture exploited in scientific production on Nursery and analyzes them according to the social-semiotic perspective of the culture. This focuses on the bibliographic research which has made use of the content analysis. The results endorse that the way social relationships get closer to one another in the globalized world suggests a re-conception of culture not as a pre-existential and compact system which differs one society from the other one, but as a set of production social processes, flow and consumption of meaning on the social life. Under this viewpoint, we conclude the professional of Nursery and so the client / user are charaters who perceive and organize symbols and meanings together and get in touch and interact themselves for changing and creating condition for the facing the situations which involve intercultural care on health.